Socializatio of the child throught values he receives via TV cartoon Movies - challal, bahia (Journal of Social Sciences and Humanities, 2024)
Cartoonmovies are the child’s first and favorite subject of entertainment, since they are fit his thinking and inclination.It is worth to mention tat cartoon movies have witnessed a great expantion among this impotant group in society after the flow of these cartoon movies throught different TV chanels. This ; infact , has made the child more addicted to them, as he follows them a lot. However, the most worrying and frightening issue is the non-surveillance contents of the cartoon movies to which the child is more attached and also the values they carry which can be totally immoral to the social values of the child’s milieu, for these cartoon movies are produced in socities which differ from our societies in social values, customs ; and traditions.As amatter of fact, this constitutes a socialization. The present paper analyzes the contents of two famous cartoon movies which have a great celebrity among children, namely , « sponge bob » and « gumball » ; in the study, the researchers carefully , for their study sample, one cartoon movie from two different channels in an attemps to explore how dangerous these are on child’s value formation.